Spontaneous Structural Distortion and Quasi‐One‐Dimensional Quantum Confinement in a Single‐Phase Compound. (29th November 2012) - Wang, Zhongchang; Gu, Lin; Saito, Mitsuhiro; Tsukimoto, Susumu; Tsukada, Masaru; Lichtenberg, Frank; Ikuhara, Yuichi; Bednorz, Johannes Georg
<x xml:space="preserve">Abstract</x> Oxide heterointerfaces often trigger unusual electronic properties that are absent in respective bulks. Here, direct evidence is offered for spontaneously assembled local structural distortions in a single‐phase bulk, which confine electrons to within an atomic layer with notable orbital reconstruction and coupling, close the forbidden band, induce a ferromagnetic ordering, and give rise to a strongly anisotropic, spin‐polarized quasi‐one‐dimensional electron gas. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>